Splenectomy is significantly associated with thrombosis but not with pulmonary hypertension in patients with transfusion-dependent thalassemia: a meta-analysis of observational studies - Kalamara, Tsampika-Vasileia; Dodos, Konstantinos; Vlachaki, Efthymia (Frontiers in Medicine, 2023)
Introduction: Thromboembolism (TE) and pulmonary hypertension (PH) constitute frequently occurring complications in patients with transfusion-dependent thalassemia and have been associated with splenectomy in different studies. Nevertheless, the size of the possible association varies greatly in literature. Herein, we sought to provide pooled effect estimates regarding the impact of splenectomy on TE and PH in transfusion dependent thalassemia (TDT) by retrieving relevant, available studies. Methods: We systematically searched articles published in PubMed, Cochrane library, Scopus and grey literature from inception until the 30th of May, 2023. Pooled estimates in terms of odds ratios (OR) and 95% confidence intervals (CI) were calculated according to outcome measures. Risk of bias and quality of studies were evaluated.Results: Regarding TE, 4 studies were selected for meta-analysis and the pooled data demonstrated that splenectomy was significantly associated with this outcome in TDT patients [OR=4.08, 95% CI (1.03, 16.11), p=0.04]. On the other hand, we pooled data from 7 investigating PH, and, interestingly, the quantitative analysis revealed no association between splenectomy and PH [OR=1.76, 95% CI (0.91, 3.41), p=0.1].Conclusion: Splenectomy is associated with higher risks of TE, but not with PH in patients with TDT.